2023
DOI: 10.2196/42239
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health Hazards Among Traffic Police in South Asian Countries: Protocol for a Scoping Review

Abstract: Background Occupational health hazards and injuries are an alarming concern among traffic police. Occupational injuries affect the physical, social, and mental well-being of police personnel, which has various public health implications. The evaluation of occupational health and safety policies and regulations for the traffic police relies on their occupational exposure and health hazard statistics and assessments. Objective The purpose of this scoping … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Most participants had musculoskeletal pain (45.333%) and least participants had fatigue (6%) and chronic bronchitis (6%). A similar result was found in another study, in which the highest prevalence of musculoskeletal pain was (56.1%) (Jahan et al, 2023). The standing hip carries most of the body weight and prolonged standing may cause fatigue of muscles around the hip.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Most participants had musculoskeletal pain (45.333%) and least participants had fatigue (6%) and chronic bronchitis (6%). A similar result was found in another study, in which the highest prevalence of musculoskeletal pain was (56.1%) (Jahan et al, 2023). The standing hip carries most of the body weight and prolonged standing may cause fatigue of muscles around the hip.…”
Section: Resultssupporting
confidence: 87%
“…Risks to one's health at work can come from a variety of sources, such as occupational injuries, illnesses, and diseases, long-term exposure to specific chemicals, or physically demanding work (Jahan et al, 2023). According to the International Labor Organization (2018), 2.2 million people per year, or an average of 6,000 people per day, lost their lives to work-related illnesses and accidents (Rini et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The study also showed that arguments with vehicle drivers and pedestrians due to traffic rule violations were the main stressors among the traffic police [32]. Many drivers and pedestrians in Kathmandu Valley do not adhere to traffic rules and regulations.…”
Section: Discussionmentioning
confidence: 86%